Metode Pembuatan Alat Pelindung Wajah untuk Aktifitas Olahraga berbasiskan Teknologi Multi-Materials 3Dprinting: indonesia - Riza, Rahmat; Muttaqin, Hazan Zainul (Asian Journal of Innovation and Entrepreneurship, 2025)
The face protection mask in soccer is an important tool that allows players with facial injuries to continue their soccer activities. However, it has unique characteristics such as specific face geometry and wound location. The application of the reverse engineering method combined with multi-material 3Dprinting technology was evaluated in this paper to develop a face protection mask that was comfortable to wear by a specific user. The results obtained showed that the face protection mask could conform to the specific facial contour of the user. The use of multi-material PLA combined with TPU made the inside of the mask softer when in contact with the user's skin.